Ethnoveterinary use of medicinal plants among the tribal populations of District Malakand, Khyber Pakhtunkhwa, Pakistan - Khan, Khalid; Jan, Gul; Irfan, Muhammad; Jan, Farzana Gul; Hamayun, Muhammad; Ullah, Fazal; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2023)
Background: The current study expresses that most of the peoples were dependent on the natural resources as compared to cultivated. Domestic animals play a vital role in the development of human civilization that why plants are utilized as a remedy for a variety of domestic animals, in addition to humans. The people of District Malakand were extremely correlated with the therapeutic potential of medicinal plants as ethnoveterinary medicine. Methods: The present study was conducted from January 2015 to December 2017 for observing the area and also to collect the medicinal plants. The assessment was observed deeply the knowledge concerned with the traditional uses of medicinal plant to cure the animal diseases. Animal diseases are a major constraint for the livestock owners; therefore, some strategies and measures should be adopted in near future. During the study stratified sampling were carried using the questioner and interviewed the people and followed by group discussion was employed to achieve the goals. Results: The represented study has 76 plant species belonged to 45 families. Amongst them one species was Pteridophyte belonged to family Pteridaceae, and one was Gymnosperm belonged to Pinaceae, while the rest of 74 species of 43 families were Angiosperms. The herbs were dominant with 40 species (52.6 %), followed by trees with 22 species (29.0 %), and shrubs with 14 species (18.4 %). The largest families were Fabaceae, Lamiaceae, Poaceae and Solanaceae with 5 species each, while the second largest family was Rosaceae with 4 species. The third largest families were Apocynaceae, Amaryllidaceae, Brassicaceae, and Malvaceae with 3 species each. A total of thirty-three ailments were treated with different plants species. The most common ailments treated of the animals were constipation, intestinal worms, paralysis, broken bone, diuretic, diarrhea, indigestion, tympany, itching, and jaundice. Conclusion: The presented study revealed that production of animals played an important role in the inhabitants of Malakand district. Their people have abundant traditional knowledge of ethnoveterinary plant remedies and practical experience of animal care and production. The traditional knowledge is near to extinction in near future, due to the extensively usage of modern veterinary medicine. Keywords: Fidelity level, District Malakand, Medicinal plants, Pakistan, Traditional knowledge.